2013
DOI: 10.1017/s0003055413000208
|View full text |Cite
|
Sign up to set email alerts
|

Organizing Rebellion: Rethinking High-Risk Mobilization and Social Networks in War

Abstract: R esearch on violent mobilization broadly emphasizes who joins rebellions and why, but neglects to explain the timing or nature of participation. Support and logistical apparatuses play critical roles in sustaining armed conflict, but scholars have not explained role differentiation within militant organizations or accounted for the structures, processes, and practices that produce discrete categories of fighters, soldiers, and staff. Extant theories consequently conflate mobilization and participation in rebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
171
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(174 citation statements)
references
References 58 publications
3
171
0
Order By: Relevance
“…Fortna 2004;Fearon and Laitin 2003;Collier and Hoeffler 2004;Downes 2008). 4 At the micro-level, recent research has focused mostly on the causes of killings (Kalyvas 2006;Balcells 2010, Metelits 2010, sexual violence (Wood 2008), and displacement (Steele 2010;Ibañez and Vélez 2008); the determinants of participation, mobilization, and recruitment (Arjona & Kalyvas, 2007;Humphreys & Weinstein, 2008;Parkinson, 2013;Petersen, 2001;Wood, 2003); and the individual-level effects of interventions to foster reintegration, reconciliation, and development (Humphreys and Weinstein 2007;Gilligan et. al 2011).…”
Section: Why Study Local Wartime Institutions?mentioning
confidence: 99%
“…Fortna 2004;Fearon and Laitin 2003;Collier and Hoeffler 2004;Downes 2008). 4 At the micro-level, recent research has focused mostly on the causes of killings (Kalyvas 2006;Balcells 2010, Metelits 2010, sexual violence (Wood 2008), and displacement (Steele 2010;Ibañez and Vélez 2008); the determinants of participation, mobilization, and recruitment (Arjona & Kalyvas, 2007;Humphreys & Weinstein, 2008;Parkinson, 2013;Petersen, 2001;Wood, 2003); and the individual-level effects of interventions to foster reintegration, reconciliation, and development (Humphreys and Weinstein 2007;Gilligan et. al 2011).…”
Section: Why Study Local Wartime Institutions?mentioning
confidence: 99%
“…Because qualitative study designs often lend themselves to the in-depth study of highly sensitive subject material (Kelly et al, 2011; King et al, 2013; Parkinson, 2013; Wade et al, 2005), field notes and interview transcripts would need to be anonymized prior to dissemination in order to conform with prevailing legal and ethical guidelines. Institutional Review Board concerns about participant anonymity, discussed in the PLOS policy (Bloom et al, 2014), have been identified as a leading barrier to data sharing.…”
Section: Data Sharing In Qualitative Researchmentioning
confidence: 99%
“…As a cautionary note, depending on the size of the dataset, the redaction or anonymization process could require tremendous time and effort of the investigators and could also potentially introduce errors and inconsistencies (Goffman, 2014; Lewis-Kraus, 2016). Additionally, for some studies, the nature of the research (Parkinson, 2013) may be such that any suitably redacted or anonymized transcripts might be so unserviceably thin that they would be devoid of meaningful content. Wolcott (1973) discusses this possibility in the introduction of his classic ethnography: “To present the material in such a way that even the people central to the study are ‘fooled’ by it is to risk removing those very aspects that make it vital, unique, believable, and at times painfully personal” (p. 4).…”
Section: Data Sharing In Qualitative Researchmentioning
confidence: 99%
“…Weapons need to be acquired; logistics and lodging need to be organised, and supporters and informers often need to be paid off in order for an organisation to function effectively (Petersen 2001;Wood 2008;Parkinson 2013). While conflict researchers have primarily focused on the role of natural resources as a means to boost a group's war chest, the selling off looted antiquities provides an alternative source of funding.…”
Section: Economic Incentivesmentioning
confidence: 99%